2014
DOI: 10.1016/j.canlet.2013.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis-associated protein S100A4 induces a network of inflammatory cytokines that activate stromal cells to acquire pro-tumorigenic properties

Abstract: Tumor cells have the ability to exploit stromal cells to facilitate metastasis. By using malignant melanoma as a model, we show that the stroma adjacent to metastatic lesions is enriched in the known metastasis-promoting protein S100A4. S100A4 stimulates cancer cells to secrete paracrine factors, such as inflammatory cytokines IL8, CCL2 and SAA, which activate stromal cells (endothelial cells and monocytes) so that they acquire tumor-supportive properties. Our data establishes S100A4 as an inducer of a cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 246 publications
(263 reference statements)
3
41
0
Order By: Relevance
“…The protein stock had no detectable endotoxins as assayed by Lonza Biosciences. The specificity of rS100A4 to induce cytokines has been validated previously using of a S100A4‐blocking antibody (Bettum et al ., 2014). Granulocyte–macrophage colony‐stimulating factor (GM‐CSF) and macrophage colony‐stimulating factor (M‐CSF) were purchased from R&D Systems (Oxon, UK).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The protein stock had no detectable endotoxins as assayed by Lonza Biosciences. The specificity of rS100A4 to induce cytokines has been validated previously using of a S100A4‐blocking antibody (Bettum et al ., 2014). Granulocyte–macrophage colony‐stimulating factor (GM‐CSF) and macrophage colony‐stimulating factor (M‐CSF) were purchased from R&D Systems (Oxon, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have demonstrated that macrophage phenotype and functions can be modulated by factors secreted by aggressive melanoma cells that are stimulated with extracellular S100A4 (Bettum et al ., 2014). S100A4 is a small, Ca 2+ ‐binding protein strongly associated with metastasis and poor prognosis in various cancers (Boye and Maelandsmo, 2009; Mishra et al ., 2011; Rudland et al ., 2000) and also involved in inflammatory disorders (Cerezo et al ., 2011; Grigorian et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schematic pathway for bladder cancer invasiveness development (Kader et al, 2007;Pei et al, 2014;Donmez et al, 2009;Bettum et al, 2014).…”
Section: Appendicesmentioning
confidence: 99%
“…Metastasis-associated protein 1 (MTA1) is a human protein that is encoded by the MTA1 gene (8,9). MTA1 is a protein that has been associated with the metastatic state of various cancer types (10)(11)(12)(13)(14). MTA1 promotes tumor invasion by the downregulation of E-cadherin in human esophageal squamous cell carcinoma cells (10).…”
Section: Introductionmentioning
confidence: 99%